Extraordinarius gen. nov., a new genus of Sparianthinae spiders (Araneae: Sparassidae) from southeastern Brazil - Rheims, Cristina A. (Zootaxa, 2019)
A new genus of Sparianthinae, Extraordinarius gen. nov., is proposed to include the type species, Extraordinarius andrematosi sp. nov. (♂♀), from São Paulo, E. brucedickinsoni sp. nov. (♂♀), from Minas Gerais and Espírito Santo, and E. klausmeinei sp. nov. (♂) and E. rickalleni sp. nov. (♂♀), from Espírito Santo. The genus is remarkable in that it is the only Neotropical genus of Sparianthinae with a large, sclerotized, Z-shaped conductor in the male palp and represents the southernmost record for the subfamily in the region. A distribution map is provided for all known species of the genus.